Differential expression of antibodies to NMDA receptor in anti-NMDA receptor encephalitis and in neuropsychiatric systemic lupus erythematosus. Issue 1 (13th November 2019) - Hirohata, Shunsei; Tanaka, Keiko
Abstract : Objective: Anti-NMDA receptor encephalitis is the most prevalent autoimmune encephalitis having characteristic clinical features with autoantibodies against tetrameric transmembrane channels composed of combinations of NR1 subunits of NMDA receptors with NR2 subunits, which are detected by cell-based assay (anti-NR1/NR2). On the other hand, antibodies against the linear epitope in NR2 subunit (anti-NR2) have been shown to be expressed in patients with diffuse psychiatric/neuropsychological syndromes of neuropsychiatric SLE (diffuse NPSLE). However, it has not been explored whether anti-NR1/NR2 might be detected in NPSLE, nor has it been clear whether anti-NR2 might have cross-reactivity with anti-NR1/NR2. The current study was therefore performed to explore the prevalence of anti-NR1/NR2 in NPSLE. Methods: Serum specimens were obtained from 31 patients with NPSLE (22 with diffuse NPSLE and 9 with neurological syndromes or polyneuropathy) and from 18 normal healthy subjects. Anti-NR2 and anti-NR1/NR2 were measured by ELISA and cell-based assay, respectively. The positivity for anti-NR2 was defined by a value exceeding mean+2 SD of normal healthy subjects. Results: Anti-NR2 was positive in the sera of 19 of 31 patients with NPSLE (in 15 of 22 patients with diffuse NPSLE). By contrast, anti-NR1/NR2 was positive only in 2 of 31 patients with NPSLE (in 2 of 22 patients with diffuse SLE). The positivity for anti-NR1/NR2 was not correlated with anti-NR2 values. Conclusions: These results demonstrate that the prevalence of anti-NR1/NR2 is extremely low in NPSLE. Moreover, the data also confirm that anti-NR2 antibodies do not have cross-reactivity with anti-NR1/NR2.